Gold mining taxation in South Affrica : a discussion of the MPRDA, its amendments and whether internal inconsistencies exist in the mining legislation - Dowe, Karen (School of Economics, 2024)
The purpose of this paper is to add to the current debate regarding the royalty imposition by discussing the Mineral and Petroleum Resource Development Act No. 28 of 2002 and the three amendments that have been made to it. The effect on investment, production, exploration and government taxation revenue of the MPRDA, specifically on gold mining taxation in South Africa, is discussed. An important objective of the Act is to deal with past injustices. The Act results in a change in the ownership of minerals, where all mineral rights will vest in the state. The paper analyses whether internal inconsistencies in the mining legislation exist, by comparing the effects of the introduction of royalties, ring-fencing and the 'use-it or lose-it' clause. It is found that certain inconsistencies do exist.